The role of probiotics in iron deficiency anemia management: Peran probiotik dalam manajemen anemia defisiensi besi - Siti Rachmatiara Dwi Destiarini; Sherly Horax; Marhamah; Fajriani; Sumintarti (Makassar Dental Journal PDGI Makassar, 2023)
Iron deficiency anemia (IDA) is the most common anemia in both developed and developing countries; caused by a lack of iron availability in the body, causing insufficient iron needed for the formation of red blood cells. Majority of IDA that occurs in children needs serious attention because iron deficiency has an impact on children's growth and development disorders. This type of anemia not only has general symptoms, but also has oral manifestations that can be detected in the soft tissues of the oral cavity. The IDA can occur due to impaired absorption of iron in the intestine. The existence of these malnutrition factors makes the role of probiotics one of the solutions that can be developed in the management of Iron Deficiency Anemia by helping to increase iron absorption.